Orthopaedic specialty committee exit examination amidst the COVID-19 pandemic in Malaysia- experiences and reflections from the candidates - Saaid, Firdati Mohamed; Khirul Asha, Nur Ayuni; Md Yusoff, Zuhri; Kamisan, Norazian; Ismail, Imma Isniza; Liew, Siew Khei; Arumugam, Manohar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: The emergence of the COVID-19 pandemic had affected the Orthopaedic Specialty Committee (OSC) Exit Examination candidates. The objective of this study was to evaluate the impact of this pandemic on the candidates’ teaching and learning, mental well-being, and personal experience during the examinations. Methods: A cross-sectional study was conducted from 1st to 31st January 2021. 103 candidates for the OSC Exit Examination November 2020 were asked to answer a questionnaire. Wilcoxon signed-rank tests were used to compare differences in the frequencies before and during the pandemic. A p-value of less than 0.05 was taken as significant. Results: There was a significant reduction in the number of classes (P-value < 0.001) and examination preparatory courses conducted, reduced number and variety of patients attended and limited exposure in the operation theatre. Most candidates had virtual and physical classes, and agreed virtual clinical teaching was less effective. A majority had increased caffeine intake and smoking habits, decreased time spent with family and sports activities and no impact on sleeping hours, alcohol and analgesic usage. During the examinations, most candidates felt disturbed by the COVID-19 safety protocol and worried about the risk of contracting the infections. Conclusion: The effect of this pandemic on the post-graduate Orthopaedics students teaching and learning is massive. Virtual teaching programmes or applications that can replace the traditional clinical teaching methods should be explored and developed for the benefit of our education system.